The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/cas.13860
|View full text |Cite
|
Sign up to set email alerts
|

Mutational activation of the epidermal growth factor receptor down‐regulates major histocompatibility complex class I expression via the extracellular signal‐regulated kinase in non–small cell lung cancer

Abstract: The efficacy of programmed cell death–1 (PD‐1) blockade in patients with non–small cell lung cancer (NSCLC) positive for epidermal growth factor receptor (EGFR) gene mutations has been found to be limited, but the underlying mechanisms for this poor response have remained obscure. Given that the recognition by T cells of tumor antigens presented by major histocompatibility complex class I (MHC‐I) molecules is essential for an antitumor immune response, we examined the effects of EGFR tyrosine kinase inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…Additionally, several recent studies report that MHC-I and MHC-II expression is downregulated via the IFN-γ signaling pathway and downstream MEK/ERK signaling pathways (Fig. 2) [102,[107][108][109][110][111].…”
Section: Cell Surface Molecules and Selected Soluble Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, several recent studies report that MHC-I and MHC-II expression is downregulated via the IFN-γ signaling pathway and downstream MEK/ERK signaling pathways (Fig. 2) [102,[107][108][109][110][111].…”
Section: Cell Surface Molecules and Selected Soluble Factorsmentioning
confidence: 99%
“…IFN-γ potentiates the induction of MHC class I (MHCI) and II (MHCII) molecules [102,106]. Watanabe et al found that EGFR-mutant cells have lower levels of human leukocyte antigen (HLA)-B expression than do EGFR-wildtype cells [107] in the presence of IFN-γ. Additionally, several recent studies report that MHC-I and MHC-II expression is downregulated via the IFN-γ signaling pathway and downstream MEK/ERK signaling pathways (Fig.…”
Section: Cell Surface Molecules and Selected Soluble Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MEK inhibitors trametinib and cobimetinib have been demonstrated to enhance IRF1 expression and increased STAT1 phosphorylation in human keratinocytes [188]. Watanabe et al [189] reported that treatment of a NSCLC cell line with trametinib also increased MHC-I expression in vitro. Another MEK inhibitor, selumetinib, increased MHC-I expression in papillary thyroid cancer cell lines [2].…”
Section: Well-known Oncogenic Pathways Affect Mhc-i Expressionmentioning
confidence: 99%
“…[ 17 ] Pre-clinical studies demonstrated that acquired resistance of EGFR-TKI could occur through the MEK/ERK pathway by major histocompatibility complex class I molecules down-regulation, which may be reversed by MEKi. [ 18 ] Taken together, when EGFR-TKI failure occurs in EGFR-driven NSCLC patients, we propose that combination of MEKi and immunotherapies can be considered. Further clinical trials are needed.…”
mentioning
confidence: 99%